The Physicochemical Synergy Effect of Nanosecond Pulsed Electric Fields (nsPEF) and cisplatin on reversing chemoresistance of bladder cancer - Danjing Guo; Xiao Li; Xiaobo Xu; Xinhua Chen; Hongqiang Cheng; Junhui Jiang (PLoS ONE, 2026)
Nanosecond Pulsed Electric Field (nsPEF) is an intense electrical pulse technology with ultra-short duration (nanoseconds), capable of generating electric field intensities up to several kV/cm. By inducing irreversible electroporation for tumor tissue ablation, nsPEF triggers apoptosis in cancer cells, stimulates anti-tumor immune responses, and enhances exogenous gene transfection. As a primarily non-thermal technique, it offers advantages such as minimal tissue damage, high targeting efficiency, short treatment duration, and compatibility with other therapies. Currently demonstrating broad application potential in cancer treatment. Urothelial Bladder Carcinoma (UBC), accounting for over 90% of bladder cancers, originates from the transitional epithelium of the bladder’s urothelium and represents the most common malignant tumor in the urinary system. Cisplatin (CDDP), a key chemotherapeutic agent for UBC, is particularly effective for recurrent or advanced-stage patients. However, repeated use often leads to drug resistance. This study investigates the cytotoxic effects of nsPEF on UBC cells and its inhibitory mechanisms against drug-resistant UBC. Through sustained gradient concentration induction of CDDP, we successfully established drug-resistant cell lines T24/CDDP and TCC/CDDP. After treatment with nsPEF on parental cell lines (T24, TCC) and their drug-resistant variants (T24/CDDP, TCC/CDDP), all cells exhibited time-and dose-dependent sensitivity. Western blot analysis revealed that the basal expression of γ-H2AX was significantly reduced in the drug-resistant cells (T24/CDDP, TCC/CDDP), while nsPEF treatment significantly upregulated its expression. In vivo experiments further demonstrated that nsPEF exhibited significant antitumor efficacy against tumor-bearing mice from T24/CDDP. Overall, nsPEF effectively induces apoptosis in T24, TCC, and their drug-resistant variants, with particularly potent effects on drug-resistant UBC cells. This enhanced effect may be attributed to nsPEF-induced more severe DNA damage in drug-resistant cells, as manifested by elevated γ-H2AX expression.. This study provides experimental evidence for applying nsPEF to overcome chemotherapy resistance in UBC.